Alemtuzumab based reduced intensity transplantation for pediatric severe aplastic anemia. Issue 7 (8th March 2015) - Ngwube, Alexander; Hayashi, Robert J.; Murray, Lisa; Loechelt, Brett; Dalal, Jignesh; Jaroscak, Jennifer; Shenoy, Shalini
<x xml:space="preserve">Abstract</x> Background Hematopoietic cell transplantation (HCT) is curative in patients with severe aplastic anemia (SAA). HCT is considered at presentation when a HLA‐matched related donor (MRD) is available and has a high success rate. Unrelated donor (URD) transplants are typically undertaken if immunosuppressive therapy fails. Increased toxicity and graft rejection are often encountered in this setting. Procedure We report a prospective multi‐center trial of HCT in 17 children with SAA following novel reduced intensity conditioning with alemtuzumab, fludarabine and melphalan, and the best available donor. Nine were URD transplants matched at 7–8/8 loci, and performed following failure of immune suppression. Median follow up was 61 months (range 6–128). Results All patients engrafted. Estimated 5 year event‐free and overall‐survival was 88% (95%CI 65.7–96.7). Five year overall survival for MRD and URD transplants was 100% and 78% (95%CI 45–93.6) respectively. Median times to neutrophil and platelet engraftment was 14 (range 10–27) and 23.5 (range 11–65) days respectively. Treatment related mortality was 12%. The incidence of grade II–IV and III–IV acute graft‐versus‐host disease was 29% and 18% respectively. At two years, all but one patient discontinued immunosuppression successfully. Laboratory measures of immune reconstitution normalized at one year and infection rates were low in the latter part of the first year. Conclusions HCT using this RIC approach was well tolerated and successful in achieving donor engraftment and early immune reconstitution with good quality of life free of immune suppression. Children with SAA can be successfully transplanted using alemtuzumab based conditioning. Pediatr Blood Cancer 2015;62:1270–1276. © 2015 Wiley Periodicals, Inc.